The mystery guest - Prose, Nita (2023)
"When an acclaimed author dies at the Regency Grand Hotel, it's up to a fastidious maid to uncover the truth, no matter how dirty."--
Keywords: Hotel cleaning personnel -- Fiction; Murder -- Investigation -- Fiction; Hotels -- Fiction; Detective and mystery fiction; Novels